A comparison of particulate matter and gaseous emission factors from two large cargo vessels during manoeuvring conditions - Thuy Chu-Van; Zoran Ristovski; Ali Mohammad Pourkhesalian; Thomas Rainey; Vikram Garaniya; Rouzbeh Abbassi; Richard Kimball; Nho Luong Cong; Sanaz Jahangiri; Richard J. Brown (Energy Reports, 2019)
In this study, emission factors of both particle and gaseous phases are characterised on board two large cargo vessels operating on the east coast of Australia during manoeuvring conditions. In order to investigate the difference in particle number and mass size distributions, measurements were conducted on two 2-stroke engines of two vessels using Heavy Fuel Oil (HFO) with nearly the same sulphur content. Results showed that manoeuvring compared to ocean-going conditions resulted in higher emission factors for carbon monoxide (CO), carbon dioxide (CO2), unburnt hydrocarbon (HC), particulate matter (PM) and particle number (PN), which can have significant negative effects on human health and the environment in coastal and port areas. Importantly, a significant difference was observed in particle number size distributions between the two vessels. Those observed for Vessel II were mono-modal with the peak at 40-50~nm and dominated by ultrafine particles (D < 100~nm), while for Vessel I a bimodal distribution with a nucleation peak at around 20~nm and a major peak at larger diameter of 60~nm was observed. The difference in particle number size distributions between the two vessels may be due to the difference in sampling location and/or marine engine characteristics, including age and technology. The effects of fuel sulphur content on PN and PM emissions observed in this study are also compared with the results available from previous measurements in the literature. Engine load was also found to be an important influence on all emission factors.
Keywords: 330; Emission factors; Manoeuvring conditions; Particle number size distributions; Ship emissions; Sulphur content